2013
DOI: 10.1371/journal.ppat.1003368
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Tropism of Simian Varicella Virus during Primary Infection

Abstract: Varicella-zoster virus (VZV) causes varicella, establishes a life-long latent infection of ganglia and reactivates to cause herpes zoster. The cell types that transport VZV from the respiratory tract to skin and ganglia during primary infection are unknown. Clinical, pathological, virological and immunological features of simian varicella virus (SVV) infection of non-human primates parallel those of primary VZV infection in humans. To identify the host cell types involved in virus dissemination and pathology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(100 citation statements)
references
References 54 publications
6
94
0
Order By: Relevance
“…SVV infection in nonhuman primates provides a model system with which to identify cells involved in the dissemination of varicella to multiple organs during primary infection as well as after reactivation. During experimental primary SVV infection in AGM, alveolar macrophages and dendritic cells become infected at 5 dpi and transfer virus to T cells in lymph nodes (12). In the study described here, we extended studies of SVV reactivation in rhesus macaques and demonstrated the presence of SVV in the sweat glands of skin and in the macrophages and dendritic cells of lymph nodes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…SVV infection in nonhuman primates provides a model system with which to identify cells involved in the dissemination of varicella to multiple organs during primary infection as well as after reactivation. During experimental primary SVV infection in AGM, alveolar macrophages and dendritic cells become infected at 5 dpi and transfer virus to T cells in lymph nodes (12). In the study described here, we extended studies of SVV reactivation in rhesus macaques and demonstrated the presence of SVV in the sweat glands of skin and in the macrophages and dendritic cells of lymph nodes.…”
Section: Discussionsupporting
confidence: 57%
“…SVV-seronegative rhesus macaques (monkeys HB62, HI83, HF39, HC44, HA95, II49, and IK10) were inoculated intrabronchially with 10 4 PFU of wild-type SVV (monkeys HB62, HI83, HA95, II49, and IK10) or SVV expressing enhanced green fluorescent protein (SVV-EGFP) (monkeys HF39 and HC44) as described previously (4,10). Earlier, we demonstrated that SVV-EGFP is pathogenic in African green monkeys and that SVV-EGFP is mildly attenuated compared to wild-type SVV (11,12). All monkeys were monitored by physical exams every 2 or 3 days, and blood samples were collected either weekly or biweekly.…”
Section: Methodsmentioning
confidence: 99%
“…Primary SVV infection results in viraemia ; however, SVV DNA is present in monkey ganglia prior to rash Ouwendijk et al, 2012c), indicating virus can infect ganglia during the viraemic stage of infection. This finding was recently confirmed and extended by the demonstration that SVV infects memory T-cells prior to rash and virus DNA is present in neurons, in close proximity to memory T-cells (Ouwendijk et al, 2013). In addition, VZV-infected T-cells, most likely memory T-cells (Ku et al, 2004), can transfer virus to engrafted human dorsal root ganglia in a model of VZV pathogenesis using severe combined immunodeficient (SCID) mice (Zerboni et al, 2005).…”
Section: Introductionmentioning
confidence: 61%
“…Moreover, as described for VZV, SVV can reactivate during episodes of immune suppression and stress (11)(12)(13), and this reactivation is accompanied by the upregulation of CXCL10 and T cell infiltration (14). Recent studies using African green monkeys (AGMs) inoculated with SVV-enhanced green fluorescent protein (EGFP) have shown that SVV infects T cells that infiltrate the ganglia during acute infection 9 dpi (15). However, SVV infection of AGMs, in contrast to human VZV infection, results in significant mortality (16), and SVV-GFEP is attenuated compared to the wild type (WT) (15).…”
mentioning
confidence: 99%